Pertumbuhan dan Produksi Kangkung Hidroponik Sistem DFT pada Media Semai dan Jumlah Bibit yang Berbeda Growth and Production of Water Spinach Hydroponics DFT Sistem on Seedling Media and Different Number of Seeds - Cartika, Ika; Adiwijaya, Hamdan Drian (Agropross : National Conference Proceedings of Agriculture, 2022)
Water spinach can be grown hydroponically using the DFT system. Seeding is needed before the seeds are transplanted, so it is necessary to select the appropriate seedling media because it will determine the initial growth of water spinach. The number of seeds per netpot also needs to be regulated because it affects the competition for growing space, nutrient absorption and sunlight reception. The purpose of this study was to determine the effect of seedling media and the number of seeds per netpot on the growth and production of water spinach in the DFT hydroponic system. The experiment was carried out in the Balitsa Lembang screen house from March to April 2022. The experiment used a two-factor randomized design with 3 replications. The first factor of seedling media consisted of: soil + cow manure, soil + sheep manure, and soil + subur ijo organic fertilizer. The second factor is the number of seeds per netpot consisting of: 6, 8, and 10 seeds. The results showed that the soil seedling media + sheep manure produced the highest seedling growth rate of 76.67%. 6 seedlings per netpot yielded the highest percentage of live plants, which was 96%. 6 seedlings per netpot resulted in higher plant height, stem diameter, plant weight, and harvest index than 10 seedlings, but not significantly different from 8 seedlings. Soil seedling media + sheep manure and 6 seeds per netpot can be used in DFT hydroponic cultivation of water spinach to increase production and save plant seeds.